In Vitro Synergistic Activity of Antimicrobial Combinations against Carbapenem- and Colistin-Resistant Acinetobacter baumannii and Klebsiella pneumoniae - Paraskevi Mantzana; Efthymia Protonotariou; Angeliki Kassomenaki; Georgios Meletis; Areti Tychala; Eirini Keskilidou; Maria Arhonti; Charikleia Katsanou; Aikaterini Daviti; Olga Vasilaki; Georgia Kagkalou; Lemonia Skoura (Antibiotics, 2023)
Polymyxins are commonly used as the last resort for the treatment of MDR Acinetobacter baumannii and Klebsiella pneumoniae nosocomial infections; however, apart from the already known toxicity issues, resistance to these agents is emerging. In the present study, we assessed the in vitro synergistic activity of antimicrobial combinations against carbapenem-resistant and colistin-resistant A. baumannii and K. pneumoniae in an effort to provide more options for their treatment. Two hundred A. baumannii and one hundred and six K. pneumoniae single clinical isolates with resistance to carbapenems and colistin, recovered between 1 January 2021 and 31 July 2022,were included. A. baumannii were tested by the MIC test strip fixed-ratio method for combinations of colistin with either meropenem or rifampicin or daptomycin. K. pneumoniae were tested for the combinations of colistin with meropenem and ceftazidime/avibactam with aztreonam. Synergy was observed at: 98.99% for colistin and meropenem against A. baumannii; 91.52% for colistin and rifampicin; and 100% for colistin and daptomycin. Synergy was also observed at: 73.56% for colistin and meropenem against K. pneumoniae and; and 93% for ceftazidime/avibactam with aztreonam. The tested antimicrobial combinations presented high synergy rates, rendering them valuable options against A. baumannii and K. pneumoniae infections.